Sorting waste saving gold: CSR innovation The Gade Clean and Gold PT Pegadaian Cirebon Area - Tiyarna, Achmad Ivan; Santoso, Akbar Putra; Brian, Calvino; Khumayah, Siti; Wihayati, Welly (Indonesian Journal of Multidisciplinary Science, 2024)
The Gade Clean and Gold program is a CSR program from the central Pegadain which aims to develop gold savings that specialize in each area to find waste banks in their respective regions to collaborate with and are committed to taking part in overcoming waste problems in Indonesia through waste management. Cirebon City is part of the PT (Perseudota Indonesia) The Gaga Clean And Gold program, aiming to address its significant waste problem. The purpose of this research is to explain the management of The Gage Clean and Silver program. The data is divided into primary, obtained through interviews with Public Relations and Marketing Executive employees of PT, and secondary, sourced from literature such as books, journals, and newspapers. The researchers used qualitative approach with descriptive qualitative method. The results of the research are as follows. Firstly, PT has planned The GAGE program to find information on the best waste bank information with the Financial Services Authority (OJK), approach by gathering waste bank managers and the community, budget management for waste bank infrastructure. Secondly, it motivates stakeholders by forming company awareness by providing injections of funds to waste banks to improve infrastructure facilities in the form of creating waste bank parks, renovating waste bank warehouses and providing gowes cars for waste transportation activities made by PT. Finally, the suggestions that can be given by researchers through the results of research on the management and management of the Gade clean and gold program are as following.